2012
DOI: 10.1093/ntr/nts137
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Among Southwestern Alaska Native People

Abstract: Introduction: We examined the characteristics, attitudes, beliefs, and exposure to tobacco products in a cohort of rural dwelling Alaska Native (AN) people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…This availability may also contribute to some difference in use observed between the two regions. Patterns of ST use among AN women are unlike those reported for women nationally and our results support findings for high prevalence of iqmik use by AN women reported in other studies [38,42]. The use of ST among girls and women in other countries has emerged as an important public health concern [43,44].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This availability may also contribute to some difference in use observed between the two regions. Patterns of ST use among AN women are unlike those reported for women nationally and our results support findings for high prevalence of iqmik use by AN women reported in other studies [38,42]. The use of ST among girls and women in other countries has emerged as an important public health concern [43,44].…”
Section: Discussionsupporting
confidence: 83%
“…Other research has found that female AN youth were more likely to use ST compared to male youth in Y-K [21]. Additionally, research conducted with AN people living in the Bristol Bay region, which borders the Y-K to the south, found women more likely to use iqmik compared to men [42]. Availability, tradition, and cultural beliefs may contribute to the differences we observed in iqmik use between regions.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Exposure to second-hand smoke was assessed using standard measures adapted in prior studies of tobacco use in AN adults (Benowitz et al, 2012, Renner et al, 2013). These items assessed how much time respondents were exposed to cigarette smoke in a usual day at home, work, or during social activities with response options: < 30 min, 30 min to < 1 h, 1–3 h, 4–7 h, or 8 or more hours; how many people who lived in their home (excluding the respondent) smoked cigarettes or chewed tobacco.…”
Section: Methodsmentioning
confidence: 99%